Factors Affecting Farm-specific Production Efficiency in the Savanna Zones of West Africa - Okike, Iheanacho; Jabbar, M.A.; Manyong, Victor M.; Smith, Jimmy W.; Ehui, Simeon K. (Oxford University Press, 2004)
Agricultural intensification involving greater crop–livestock interactions and integration is emerging as the most promising strategy for improving agricultural production and productivity in much of Sub-Sahara Africa. In West Africa, where this process is at various stages of evolution, 559 farm households from the Sudan Savanna (SS) and Northern Guinea Savanna (NGS) zones were studied to examine the factors affecting production efficiency. The farms in each zone were divided into four socio-economic domains using a combination of population density and market access as criteria. Estimation of stochastic frontier production function indicated the need to include ecological and socioeconomic variables in both the production function and the accompanying inefficiency equation, failing which such models may suffer from omitted variables bias. The results showed that inefficiency effects of a stochastic nature existed among the sample farms and average efficiency was 76%: 68% in the SS and 86% in the NGS zones. Further, increased resource use associated with agricultural intensification was not always accompanied by an increase in production efficiency; and while agricultural intensification based on high external input strategies yields higher marginal returns in the NGS, a similar strategy is not critical to success in the SS given current use levels and the biophysical endowments of the latter ecological zone.